CMV-Related Gastric Ulcer and Gastroduodenitis in an Immunocompetent Patient: A Case Report and Literature Review - Andrawus Beany (Hindawi Limited, 2021)
Background. Cytomegalovirus (CMV)- related gastroduodenal infection is rare in immunocompetent hosts, and although it is considered a self-limiting condition in most cases, there is scarce literature to assert its management. Case Presentation. We report a case of a 66-year-old immunocompetent male patient diagnosed with a giant gastric ulcer caused by CMV infection. The ulcer manifested as refractory vomiting and melena. Rapid and full resolution was observed on proton-pump inhibitor (PPI) monotherapy. Conclusion. Gastric CMV infection might mimic an advanced gastric tumor in individuals with an intact immune system. The condition is rare, and the diagnosis is challenging and oftentimes overlooked. However, a rapid resolution has been documented in all cases, even without antiviral therapy.